Epicardial left atrial appendage AtriClip occlusion reduces the incidence of stroke in patients with atrial fibrillation undergoing cardiac surgery. Issue 7 (18th July 2017) - Caliskan, Etem; Sahin, Ayhan; Yilmaz, Murat; Seifert, Burkhardt; Hinzpeter, Ricarda; Alkadhi, Hatem; Cox, James L; Holubec, Tomas; Reser, Diana; Falk, Volkmar; Grünenfelder, Jürg; Genoni, Michele; et al.
Abstract: Aims: Left atrial appendage (LAA) occlusion has emerged as an interesting alternative to oral anticoagulation (OAC) for stroke prevention in patients with atrial fibrillation (AF). We report the safety, efficacy, and durability of concomitant device-enabled epicardial LAA occlusion during open-heart surgery. In addition to long-term follow-up, we evaluate the impact on stroke risk in this selected population. Methods and results: A total of 291 AtriClip devices were deployed epicardially in patients (mean CHA2 DS2 -VASc-Score: 3.1 ± 1.5) undergoing open-heart surgery (including isolated coronary artery bypass grafting, valve, or combined procedures) comprising of forty patients from a first-in-man device trial (NCT00567515) and 251 patients from a consecutive institutional registry thereafter. In all patients ( n  = 291), the LAA was successfully excluded and overall mean follow-up (FU) was 36 ± 23months (range: 1–97 months). No device-related complications were detected throughout the FU period. Long-term imaging work-up (computed tomography) in selected patients ≥5years post-implant (range: 5.1–8.1 years) displayed complete LAA occlusion with no signs of residual reperfusion or significant LAA stumps. Subgroup analysis of patients with discontinued OAC during FU ( n  = 166) revealed a relative risk reduction of 87.5% with an observed ischaemic stroke-rate of 0.5/100 patient-years compared with what would have been expected in a group of patients with similar CHA2 DS2 -VASc scores (expected rate of 4.0/100 patient-years). No strokes occurred in the subgroup with OAC. Conclusion: The long-term results from our first-in-man prospective human trial plus our institutional registry of epicardial LAA occlusion with the AtriClip in patients with AF undergoing cardiac surgery demonstrate the safety and durability of the procedure. In addition, our data are suggestive for the potential efficacy of LAA occlusion in reducing the incidence of stroke. If validated in future large randomized trials, routine LAA occlusion in patients undergoing cardiac surgery (with contraindications to treatment with oral anticoagulants) may represent a reasonable adjunct procedure to reduce the risk of future stroke. Clinical Trial Registration: URL: http://www.clinicaltrials.gov . Unique identifier: NCT00567515.